The Degree of Parents' Practice of The Good Role Model Style Included in Islamic Educational Thought from The Point of View of University Students - AL-Momani, Mohammad Omar (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
The study aimed to identify the degree of parents' practice of the good role model style included in Islamic educational thought from the point of view of children at the university stage and its relationship to some variables such as gender, academic specialization and academic stage, where the researcher followed the descriptive analytical approach by applying the questionnaire consisting of (10) paragraphs, which served as a study tool that was applied to (2500) male and female students from various Jordanian universities in the second semester of the academic year (2023/2024), where the study concluded, after conducting the appropriate statistical treatments, that the level of parents' practice of the good role model style included in Islamic educational thought in general came at a (high) degree on the scale as a whole with an arithmetic mean of (4.42) and a standard deviation of (0.60), and the results also concluded that there were no statistically significant differences attributed to the study variables, which are gender variables (males, Females) and the variable of the type of academic specialization of the student (scientific, humanities) and the variable of the academic stage of the student (intermediate diploma, bachelor's).